2018
DOI: 10.1186/s12890-018-0581-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of COPD among pneumoconiosis patients at an occupational disease prevention institute: a cross-sectional study

Abstract: BackgroundPneumoconiosis may play an important role in the development of chronic obstructive pulmonary disease (COPD), and the complication of COPD may impose a heavy burden of illness.MethodsThe study was conducted in Hunan Province in China from December 1, 2015, to December 1, 2016. Consecutive underground male pneumoconiosis patients employed for at least 1 year were recruited from the Hunan Occupational Disease Prevention Institute. Patient information, respiratory symptoms and clinical data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 34 publications
0
21
1
1
Order By: Relevance
“…Never-smoking working miners with CWP, identified by a chest radiograph as part of a voluntary surveillance programme, had a significantly higher prevalence of ATS/ERS airflow obstruction (16.4%) and moderate/severe airflow obstruction (3.5%) compared with those without CWP (7.5% and 1.0%, respectively), and airflow obstruction was more common in miners with PMF compared with those with simple CWP. A study of non-smoking Chinese underground miners with pneumoconiosis, identified in a clinical setting, reported the prevalence of Global Initiative for Chronic Obstructive Lung Disease (GOLD)-defined chronic obstructive pulmonary disease among these miners was 18.7% 9. In our study, airflow obstruction prevalence was highest in never-smoking miners with PMF (32.3%), indicating severe cases of pneumoconiosis can present with an obstructive pattern regardless of smoking status.…”
Section: Discussionmentioning
confidence: 48%
“…Never-smoking working miners with CWP, identified by a chest radiograph as part of a voluntary surveillance programme, had a significantly higher prevalence of ATS/ERS airflow obstruction (16.4%) and moderate/severe airflow obstruction (3.5%) compared with those without CWP (7.5% and 1.0%, respectively), and airflow obstruction was more common in miners with PMF compared with those with simple CWP. A study of non-smoking Chinese underground miners with pneumoconiosis, identified in a clinical setting, reported the prevalence of Global Initiative for Chronic Obstructive Lung Disease (GOLD)-defined chronic obstructive pulmonary disease among these miners was 18.7% 9. In our study, airflow obstruction prevalence was highest in never-smoking miners with PMF (32.3%), indicating severe cases of pneumoconiosis can present with an obstructive pattern regardless of smoking status.…”
Section: Discussionmentioning
confidence: 48%
“…The present study also found that over half (57.0%) of the patients were smokers and that the prevalence of COPD did not differ between smokers and non-smokers-these findings are in line with the data previously reported. 21 While these earlier studies are not directly comparable, the data indicate that combined COPD and pneumoconiosis occurs often in patients with certain types of pneumoconiosis.…”
Section: Discussionmentioning
confidence: 85%
“…A cross-sectional study of patients with silicosis or coal workers' pneumoconiosis from South China reported a COPD prevalence of 18.65% (119/638), which is lower than our finding. 21 One reason may be that our study had a higher percentage of smokers. It is also possible that the differences in COPD prevalence are a result of other differences in study participants and working conditions.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations